FORMATION OF PROFESSIONAL AND PEDAGOGICAL FUTURE TEACHER ORIENTATIONS AS FUNDAMENTALS HIS PEDAGOGICAL CULTURE - Moiseyenko, R.M. (Pedagogy of Higher and Secondary Education, 2022)
The author in the article determines the result of research on the problem of professional and pedagogically-oriented forming as basic part of teacher’s culture.